MACHINING TIME OPTIMIZATION OF SURFACE FINISHING CNC MILLING PROCESS ON STEEL WORKS 2311 - Kriswanto Kriswanto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2023)
The rapid development of manufacturing technology is a challenge for manufacturing industry players,especially in CNC milling machining to be able to produce quality products and have an optimalmachining time speed so that high product quantities are achieved with low production costs.Therefore, small industry players now have problems with their CNC milling machines. The existingengine is relatively smaller and there are some limitations that make it a problem such as limited enginerpm and soon. All the existing problems, further research needs to be done to optimize all the needs ofthe industrial world today, especially regarding the time of the production process that needs to beoptimized. This research was conducted by varying all related parameters, starting from spindle speed,feed rate and depth of cut. In the implementation process, this research uses the Taguchi OrthogonalArray method to minimize experimental tests so that it is more time and cost efficient. The resultsobtained in this study are feed rate is the most influential parameter on machining time, followed byspindle speed and the third significant parameter is depth of cut with the smallest contribution tomachining time. Then for the most optimal design, there is the 3rd parameter design which has the mostoptimal time, which is 55 seconds